Sub-THz channel measurement and hybrid channel modeling for indoor scenarios - WANG Yang; ZHOU Xue; ZHENG Xiangquan; LIAO Xi; ZHOU Xianrong; CHEN Qianbin (Tongxin xuebao)
In response to the challenge posed by the limitations of traditional Quasi-Deterministic channel models in accurately characterizing the properties of indoor sub-THz channels, a Quasi-Deterministic hybrid channel modeling model for the sub-terahertz band was proposed. Firstly, considering the multipath sparse cluster characteristics of the sub-THz channel, the deterministic part was modeled by tracking the line-of-sight path and the low-order reflection path using the mirror method. Then, combining 220 GHz hall and 132 GHz corridor indoor scene measurements, using the extended SV (Saleh Valenzuela) model, the scattering paths within deterministic clusters and random clusters were separately counted, with a log-normal distribution describing the multipath distribution within clusters, thus completing the modeling of the stochastic component. The impulse response of the hybrid channel <alternatives>h <?fx-imagestate width="1.60866666" height="2.28600001"?> <?fx-imagestate width="1.60866666" height="2.28600001"?> </alternatives> was obtained by adding the deterministic channel impulse response <alternatives>hD <?fx-imagestate width="3.30200005" height="3.21733332"?> <?fx-imagestate width="3.30200005" height="3.21733332"?> </alternatives> and the random channel impulse response <alternatives>hS <?fx-imagestate width="2.96333337" height="3.21733332"?> <?fx-imagestate width="2.96333337" height="3.21733332"?> </alternatives>. Generally, the accuracy of the hybrid model was verified by Kolmogorov-Smirnov test, and its validity was confirmed by comparing the root-mean-square error and structural similarity indices of the small scale parameters of the extended SV model. The results demonstrate that the proposed model can accurately and effectively characterize the sub-THz channel.